Using graphics of logarithmic concentration (GLC) in the titration of bases with strong acids - Phuong Diep, Dao Thi; Thanh Mai, Nguyen Thi; Thuy Linh, Phan Thi; Luong Yen, Luu Thi (Vietnam Journal of Chemistry, 2012)
In an acid – base titration reaction, it is important to have a suitable indicator which experiences a change in color (an end point) as close as possible to the equivalence point (EP) of the reaction. Due to the appearance of the titration jump on the titration curve, we can choose any acid–base indicator which has the pT value ranging within the titration jump with an allowable error [1, 2]. The graphics of logarithmic concentration method [3, 4] has been used to evaluate exactly the pH of the acid, base solutions [5, 6]; to determine the pH at the equivalence point (pHEP) and the titration jump in the titration of acids with strong bases [7]. In this report, we study the applications of GLC in the titration of bases and mixture of bases with acids.